Isomerization of 1,5-Hexadiene Catalyzed by Bis-(Cyclopentadienyl) Lanthanide Schiff Base/NaH Systems; Ln = Sm, Dy, Y, Er (Biological Sciences - PJSIR, 2005)
Catalytic isomerization of 1,5-hexadiene by Cp Ln Schiff base/NaH (Schiff base = C  H  NO , Ln = Sm, Dy, Y,and Er) systems was studied. The isomerization resulted in a mixture of 1,4-hexadiene, 2,4-hexadiene, 1,3-hexadiene, methylene-cyclopentane, and methylcyclopentene. 1,4-Hexadiene and methylenecyclopentane were the intermediate products, while 2,4-hexadiene and methylcyclopentene were the end-products. The effects of the nature of catalyst, temperature, amount of the catalyst, time and solvent, on the isomerization rate and product composition were also stu- died. The ratio of the linear to the cyclic product in the reaction depended on the amount of catalyst used.